Diversity and dispersal of the ophiostomatoid fungus, Knoxdaviesia proteae, within Protea repens infructescences - Aylward, Janneke (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.